PARADIGMA BUDAYA ISLAM- JAWA DALAM GEREBEG MAULUD KRATON SURAKARTA - Ahmad Adib; Kundharu Saddhono (Al Qalam, 2018)
In an attempt to spread Islamic teaching, Karaton (Javanese royal kingdom) Surakarta along with Walinsongo, nine saints spreading the religion in Java, designed the annual ritual, Grebeg Maulud, to celebrate the birth of Muhammad. The ritual, which is still held until now, symbolizes the generosity of the Surakarta King. The ritual also conceals many other valuable traditional values. In order to uncover them, this study explores the historical backgrounds that underlined the commencement of the ritual This study also examines the symbolical meaning and function as well as the structure and the working procedures of the ritual Besides, this study explores the Javanese-Islamic values as represented by Grebeg Maulud's Gunungan, mountain-shaped rice presented by the Karaton on Muhammad's birthday. To collect data, this study used historical literatures obtained from various references and information provided by sentana dalem (King's inner circles), religious figures, cultural experts, academicians and society in general This study has found that Karaton Surakarta's Gunungan still serves a traditional ritual although there has been some shifting over the time as reflected by the decreasing number of presented Gunungan. Initially, there were 12 Gunungan presented in every annual Grebeg Maulud. However, in the last couple of years, there are only around two until seven Gunungan presented by the Karaton. This study has also found that over the years, the ritual is still popular in society as many are interested to come when the Gunungan is presented. People are still eager to compete with each other to grab a piece of the Gunungan.